Редупликация актантов в предикативных конструкциях(Actant Reduplication in Predicative Constructions) - Lönngren, Lennart (Poljarnyj vestnik, 2001)
This paper is an attempt to account for the following kind of para- phrasability: Edison invented the electric bulb - Edison was the inventor of the electric bulb. The proposal is that in the last sentence the holder of the first actant position has been reduplicated (Edison + inventor) with the predicate morphologically incorporated in the word inventor. In the same vein similar constructions are investigated, for instance Who is the author of this book?, She was the object of his yearning.